1968 in Europe - Klimke, M. author. aut Link
VIII, 344 p.
Keywords: A concise reference for researchers on the protest movements of the 1960s and 1970s, this book covers the history of the various national protest movements, the transnational aspects of these movements, and the common narratives and cultures of memory surrounding them.